Pharmacological and non-pharmacological treatment preferences of healthcare professionals and proxies for challenging behaviors in patients with dementia. (18th April 2017) - Janus, Sarah I.; van Manen, Jeannette G.; van Til, Janine A.; Zuidema, Sytse U.; IJzerman, Maarten J.
ABSTRACT: Background: Prescribing antipsychotics to patients with neuropsychiatric symptoms is a matter of concern. Physicians have to make treatment decisions for patients with dementia together with proxies and/or nurses. However, it is unknown whether physicians, nurses, and proxies' treatment preferences are aligned; hence this study. Methods: Sixteen treatment attributes were selected to elicit the preferences of physicians and nurses. Ten of these attributes were used for the proxies. Preferences were estimated using a case-1 Best-Worst-Scaling design; respondents are asked to select the best and worst attribute on being presented with a hypothetical patient with dementia demonstrating neuropsychiatric symptoms. The treatments offered are: antipsychotic treatment or non-pharmaceutical regimens. Results: The questionnaire was filled in by 41 physicians, 81 nurses, and 59 proxies. The non-pharmacological treatment option was chosen by 52% of the proxies and 71% of the physicians and nurses. The respondents who chose antipsychotics rated the aspects "fastest result" and "most effective" as important. Physicians ranked "experience with antipsychotics" as an important aspect for prescribing antipsychotics. Only the proxies rated the aspect "having a low negative effect on the patient" as important. The nurses and elderly care physicians who chose the non-pharmaceutical treatment ranked "appropriateness" and "of little burden to the patient" as important aspects. Conclusions: While doctors and nurses prefer non-pharmacological interventions, proxies indicated a preference for pharmacological treatment because of the immediate effect. However, physicians follow treatment guidelines and nurses and proxies rely on the physician's recommendations. We suggest physicians should be sensitive to these differences.